A Descriptive Study to Assess Knowledge Regarding POSH Act Among Staff of Chirayu Medical College and Hospital, Bhopal, Madhya Pradesh - Jyoti Majumdar (International Journal of Community Health Nursing And Practices, 2025)
Introduction: Sexual harassment is a significant health issue with severe effects on employees’ self-respect, physical mental health, and dignity. This descriptive study aimed to assess knowledge scores regarding the POSH (Prevention of Sexual Harassment) Act among staff of Chirayu Medical College and Hospital. A convenience sampling method was employed, and data were gathered using a self-designed knowledge questionnaire. The findings indicated that 41% of the staff had poor knowledge, while 59% had average knowledge about the POSH Act. No significant correlation was found between knowledge levels and socio-demographic factors. The study concluded that there is a lack of knowledge among staff regarding the POSH Act, which needs to be addressed and make them aware of this Act to ensure employees’ safety and well-being. Methodology: This descriptive study was conducted with the employees of Chirayu Medical College and Hospital. A convenience sampling method was employed, and data were gathered using a self-designed knowledge questionnaire. The questionnaire consisted of 30 items on knowledge about the POSH Act. Results: The results showed that 41% of staff had poor knowledge, and 59% had average knowledge regarding the POSH Act. No significant relationship was found between knowledge and socio-demographic variables. Discussion: The study’s results indicate a knowledge gap among the staff concerning the POSH Act. This lack of awareness can be linked to several factors, such as insufficient training and awareness initiatives. Conclusion: The study concluded that enhancing staff knowledge about the POSH Act is essential. This can be accomplished by implementing regular training sessions and awareness programs. The study’s findings have implications for nursing research, education, administration, and practice
Keywords: Assess; Harassment; Knowledge; POSH Act; Sexual